2011
DOI: 10.1186/1477-7827-9-84
|View full text |Cite
|
Sign up to set email alerts
|

Extended letrozole regimen versus clomiphene citrate for superovulation in patients with unexplained infertility undergoing intrauterine insemination: A randomized controlled trial

Abstract: BackgroundThe aim of this randomized controlled trial was to compare the efficacy of extended letrozole regimen with clomiphene citrate in women with unexplained infertility undergoing superovulation and intrauterine insemination (IUI).MethodsTwo hundred and fourteen patients with unexplained infertility were randomized into two equal groups using computer generated list and were treated by either letrozole 2.5 mg/day from cycle day 1 to 9 (extended letrozole group, 211 cycles) or clomiphene citrate 100 mg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
78
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 31 publications
6
78
0
1
Order By: Relevance
“…The current study reported a clinical pregnancy rate of 25% and a live birth rate of 21.3% for the total letrozolestimulated cycles, regardless of the ovulation triggering protocol; the rates that accord with those formerly stated in various studies evaluated letrozole superovulation in women with UI (table 4) [11][12][13][14][15][16] . However, dual triggering by FSH/hCG compared to hCG alone improved the outcome of Letrozole-stimulated IUI cycles manifested as significantly higher pregnancy rate pre-cycle (12.5% vs. 5.8%: p=0.049) and per-woman (33.33% vs. 16.67%: p=0.049), and a significantly higher live birth rate (29.6% vs, 12.5%; p= 0.039).…”
Section: Discussion:-supporting
confidence: 74%
See 2 more Smart Citations
“…The current study reported a clinical pregnancy rate of 25% and a live birth rate of 21.3% for the total letrozolestimulated cycles, regardless of the ovulation triggering protocol; the rates that accord with those formerly stated in various studies evaluated letrozole superovulation in women with UI (table 4) [11][12][13][14][15][16] . However, dual triggering by FSH/hCG compared to hCG alone improved the outcome of Letrozole-stimulated IUI cycles manifested as significantly higher pregnancy rate pre-cycle (12.5% vs. 5.8%: p=0.049) and per-woman (33.33% vs. 16.67%: p=0.049), and a significantly higher live birth rate (29.6% vs, 12.5%; p= 0.039).…”
Section: Discussion:-supporting
confidence: 74%
“…These results agree with numerous studies reported the lower incidence of multiple gestations and OHSS in letrozole-stimulated cycles [11,14,15] . These advantages may be attributed to the short half-life of letrozole with no depletion of estrogen receptors; therefore; the normal central feedback mechanisms remain intact creating a higher probability of monofollicular growth [4] .…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Only one study [29] reported significantly higher CPR with letrozole, but the difference could be explained by the very low CPR found with CC (23.07 vs. 10.68%, p < 0.001). Fouda and Sayed [30] , in an RCT of 214 women with unexplained infertility undergoing IUI, compared an extended letrozole regimen (2.5 mg cycle days 1-9) with CC and reported significantly higher CPR with letrozole [30] . The rationale behind the extended letrozole regimen is that it can improve pregnancy rates by inducing multiple ovulations [31] .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the number of mature follicles was comparable between the 2 groups, but the number of intermediate follicles was significantly higher in the CC group. Results from studies comparing the number of follicles are heterogeneous, and no correlation with multiple pregnancy rates has been reported [26][27][28][29][30] . We found no difference in the multiple pregnancy rates, confirming the results reported in the literature [25,[28][29][30] .…”
Section: Discussionmentioning
confidence: 99%